Credit shocks and their impact on banking profitability – An applied study on the Iraqi National Bank for the period (2004-2016) – Iraq – - Al-Abedi, Amar Yasir AbdulKadhim; Hashim, Karrar Mohammed Ridha (Journal of Risk and Crisis Management, 2021)
The research aims to identify the impact of credit shocks on the profitability of the bank and after studying and identifying research variables, and after data has been collected on the research sample and it (the National Bank of Iraq) for a period of (2004-2016), these data were subjected to several tests including multiple statistical self-regression and simple regression through the use SPSS software V.25, Minitab v.18, and research found a set of practical results, including the effect that there is a significant relationship between credit shocks and profitability of the bank at a significant level (0.05) of the Iraqi National Bank, the research has presented a number of recommendations, including the need for attention by the banks management research sample and banks and other study of credit negative shocks and knowledge of its causes in order to play by reducing and address them, enabling them to build a strong reputation contribute to the achievement of high performance banking on the mid-level and long-term thing which is reflected positively in achieving profitability, As well as the need for the bank to maintain a suitable financial stock to face negative shocks, which contributes to the survival of the bank as long as possible in the market, preserving its position.
Keywords: credit shock; bank profitability; bank credit